Looking behind the fading feminist façade of #Girlboss - Cornelia Kees (Junior Management Science (JUMS), 2025)
This study investigates the media representation of female entrepreneurs in newspaper and magazine articles from 2014 to 2022. By employing a quantitative content analysis of 192 articles, the study examines dominant narratives, entrepreneurial identities, ethical behaviors, challenges depicted, and tone used across various mediums and countries, thereby addressing a gap in literature focused on single media or country contexts. Results indicate a predominantly positive portrayal of female entrepreneurship, often framed within a heroic narrative. Representations of entrepreneurial femininities are conspicuously underrepresented in the analyzed articles, with relational entrepreneurial femininity prevailing as the principal depiction. However, while ethical behaviors are more frequently highlighted than non-ethical ones, attributes of female entrepreneurs as innovative or genius are notably absent. The most commonly cited challenge is resource constraints. These insights suggest that while entrepreneurship remains a male-dominated concept in media, positive depictions of female entrepreneurs and their relevant skills are emerging, potentially inspiring and supporting future female entrepreneurs.
Keywords: 650; entrepreneurial femininity; ethical behaviour; female entrepreneurship; media portrayal; sentiment analysis